Efectividad de la actualización en bioaerosoles dirigida a estudiantes de la Universidad Antonio Nariño, sede Bucaramanga. - Gazcón Ochoa, Paula Andrea; Ibarra Ortiz, Andrea Dubeiby (Universidad Antonio Nariño, 2021)
Some dental procedures represent to a great extent a risk for the health professional, since in practice they are exposed to biological risks due to the production of bioareosols which can contain microorganisms, such as fungi, viruses and bacteria that can cause infectious diseases.